#TITLE_ALTERNATIVE# - PUTRI PRIMADIYANTI (NIM: 26912011), SUCI
Asphalt sensitivity to the temperature differences will make properties of a mixture depend on the properties of asphalt which enveloped it. The improvement of the rheological properties of the asphalt, is expected to obtain a mixture performance that is more resistant to temperature while it still having a good performance in resisting traffic loads during itÃ‚Â’s service life. From the previous rheological properties of asphalt research, optimum levels obtained is in the proportion of 10% asphalt. To observe the effect of the application improvement of the rheological properties of the asphalt in the asphalt mixture, this study conducted 3 levels of asbuton in mixture asphalt proportion of 0%, 5% and 10%. The physical properties of asphalt were tested and compared using the specification of Bina Marga 2010, while the performance of the mixture obtained by the Marshall test, the Resilient Modulus tested by UMATTA and Fatigue performance using 4-Point Bending Test. The physical properties of asphalt testing showed that 10% Asbuton has a smallest value of penetration, the highest penetration index value and softening point. Marshall test results indicate that the increased levels of Asbuton in 60/70 pen bitumen can increase the Marshall Stability. Based on test results UMATTA, the highest Resilient modulus values at temperatures of 20oC (5322 MPa) and 45oC (295 MPa) was AC-BC mixture with 10% Asbuton. The results of fatigue test (with 4 point loading) showed that the highest resistant to fatigue on almost all the strain and fatigue life of the mixture is in the mixture with 10% Asbuton within the bitumen mix. In general, the test results showed that the mixture of AC-BC, bitumen 60/70 Pen grading 10% Asbuton gives the best performance to the value of flexibility in terms of stiffness and resistance to cracking, so, is promoted to be used as an alternative in the repair of pavement performance.